Role of Interleukin-32 in Helicobacter pylori-Induced Gastric Inflammation - Sakitani, Kosuke (American Society for Microbiology, 2012)
Helicobacter pylori infection is associated with gastritis and gastric cancer. An H. pylori virulence factor, the cag pathogenicity island (PAI), is related to host cell cytokine induction and gastric inflammation. Since elucidation of the mechanisms of inflammation is important for therapy, the associations between cytokines and inflammatory diseases have been investigated vigorously. Levels of interleukin-32 (IL-32), a recently described inflammatory cytokine, are increased in various inflammatory diseases, such as rheumatoid arthritis and Crohn's disease, and in malignancies, including gastric cancer. In this report, we examined IL-32 expression in human gastric disease. We also investigated the function of IL-32 in activation of the inflammatory cytokines in gastritis. IL-32 expression paralleled human gastric tissue pathology, with low IL-32 expression in H. pylori-uninfected gastric mucosa and higher expression levels in gastritis and gastric cancer tissues. H. pylori infection increased IL-32 expression in human gastric epithelial cell lines. H. pylori-induced IL-32 expression was dependent on the bacterial cagPAI genes and on activation of nuclear factor κB (NF-κB). IL-32 expression induced by H. pylori was not detected in the supernatant of AGS cells but was found in the cytosol. Expression of the H. pylori-induced cytokines CXCL1, CXCL2, and IL-8 was decreased in IL-32-knockdown AGS cell lines compared to a control AGS cell line. We also found that NF-κB activation was decreased in H. pylori-infected IL-32-knockdown cells. These results suggest that IL-32 has important functions in the regulation of cytokine expression in H. pylori-infected gastric mucosa.